Lower insulin sensitivity in young adults born preterm in Thailand - Kittipan Rerkasem (2020)
© 2019 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd Background: Previous studies reported impaired glucose homeostasis among preterm survivors, but consisted almost exclusively of Caucasians. It is unknown whether Asians born preterm display similar impairments. Aim: To assess glucose homeostasis and other cardiometabolic outcomes among young adults born preterm in Thailand. Methods: Participants were 575 young adult offspring of mothers from the Chiang Mai Low Birth Weight Study, born in 1989 to 1990 and followed up in 2010: 54.1% females, median age 20.6 years, including 33 individuals (5.7%) born preterm. After an overnight fast, participants underwent clinical assessments, including blood sampling (glucose, insulin, and lipid profile). Insulin sensitivity was assessed using HOMA-IR and insulin secretion estimated using HOMA-β. Results: In unadjusted analyses, young Thai adults born preterm were 3.2 cm shorter (P =.037), 6 kg lighter (P =.016), and had HOMA-β 34% higher (P =.026) than those born at term. Adjusted analyses accounting for important confounders showed marked impairments in glucose homeostasis among preterm survivors: fasting insulin levels were 32% greater (P =.011), with HOMA-IR and HOMA-β that were 31% (P =.020) and 43% higher (P =.005), respectively, compared to peers born at term. There were no other contrasting observations between groups, with anthropometric differences disappearing after adjustment for confounders. Discussion: Young adults in Thailand born preterm were more insulin resistant than peers born at term. The observed impairments in glucose metabolism among young Thai adults born preterm corroborate findings reported mostly on Caucasians. The challenge for general practitioners and public health professionals is to encourage those born preterm to make healthier lifestyle choices early on.